Editorial - Bernardo-Fiho, Mario (Brazilian Journal of Health and Biomedical Sciences, 2020)
The coronavirus pandemic is disrupting the personal lives of the populations across the world, including universities and research institutes. Unusual words have been normally used, such as social distancing, isolation, quarentine, and lockdown to try to avoid the spread of the virus, and to minimize the undesirable conditions of the COVID-19 pandemic. Nevertheless, universities and research institutes are working very hard to find out how the disease can be stopped and its effects mitigated. Medications are under study and there are efforts towards the prompt availability of vaccines to the populations. At the same time, there is not a clear strategy defined with medications and vaccines; the use the facial masks and frequent washing hands have been also stimulated. There are ongoing researches related to the COVID-19 in several topics, and there is a growing number of publications in this topic. Several scientific journals, in various countries, are publishing papers on the COVID-19 outbreak and so is the Brazilian Journal of Health and Biomedical Sciences (BJHBS). The current issue (2020/1) has papers in various subjects. In the originals section, the first is about the COVID-19 and it shows the work process and mental health care at the Psychosocial Care Center of the Universidade do Estado do Rio de Janeiro (CAPS UERJ) in the COVID-19 pandemic. The aim was to report and analyze the reorganization of CAPS UERJ’s work processes, in view of the public political virtue that determines social distance in the midst of the COVID-19 pandemic, considering its specificities and its commitment to territorial logic. A Randomized Controlled Trial investigated the acute musculoskeletal and cognitive effects of stochastic resonance whole-body vibration (SR-WBV). The individuals were allocated randomly in a verum (6 Hz, SR-WBV) or sham (2 Hz, SR-WBV) condition. Inhibitory control was measured with the Stroop Test before and after the exercise. Also, muscle stiffness, muscle relaxation, sense of balance and surefootedness were assessed in a questionnaire before and after the exercise. The findings indicated that S-WBV seems to be an appropriate method to improve not only physiological measurements but newly also cognition, i.e. inhibitory control. SR-WBV exercise reduces interference and increases inhibitory control in a young and healthy sample. An association between severe chronic periodontitis (PD) and cutaneous microvascular reactivity in hypertensive patients is presented. PD is characterized as a destructive disease that affects the tissues that support the teeth, reaching gums, periodontal ligaments, cement and alveolar bone. It aimed to evaluate a possible association between severe chronic periodontitis on cutaneous microvascular reactivity in hypertensive patients, as well as to verify relationship between body adiposity and PD in a clinical study. Venous ulcers (VU) is the subject of the next original paper. The VU generate physical, emotional, social and economic changes for patients, and the occurrence of infection in these wounds aggravates this situation. The article is entitled “Performance of Hidrofiber technology and Ag+ EXTRA technology as a cover for infected VU” and it aimed i) to identify the socioeconomic characteristics of patients with infected venous ulcers selected for the study; ii) to describe the intensity of pain reported by patients, during the dressing removal procedure; and iii) to analyze the evolution of clinical signs of infection of infected VU during the treatment of lesions with Hidrofiber technology and Ag + EXTRA technology for five weeks. Review articles cover various topics: the present edition brings a narrative review about inflammatory bowel disease (IBD) women’s sexual and reproductive health. IBD is a chronic idiopathic condition involving the gastrointestinal tract. The disease prevalence is increasing worldwide, affecting women in childbearing age. The aim was to present an approach of clinical and practical review of the women´s sexual and reproductive health in IFD with focus in gynaecological and obstetrical management. Empathy is defined as a psychological process guided by mechanisms that encompass the affective, cognitive and behavioral spheres regarding the observation of the other’s experience, essential to the medical field in establishing trust between doctor and patient. The second review of the issue aimed to identify the variables that can influence the levels of empathy during medical graduation, such as gender, year of graduation and choice of medical specialty. Editorial 10 bjhbs.hupe.uerj.br The benefits of the hot tub in reducing pain in preterm newborns (PTNB) is the subject of the last paper, presented as an integrative review. PTNB is the baby born after the termination of pregnancy before completing 37 weeks of gestation. In view of the numerous consequences of this early birth, the sensation of pain is identified with greater intensity, as its inhibitory pathways are not fully developed in the PTNB. This integrative review concludes that, possibly, hot tub is able to offer PTNB a humanized approach, considered one of the most indicated techniques. Finally, a case report involving a female patient with psoriasis on irregular treatment with methotrexate, folic acid, and cyclosporine presenting erythroderma associated with epidermal desquamation, mucositis and pancytopenia is discussed. The COVID-19 has affected directly the professional lives of the individuals, including those involved in the preparation of the journals. In the case of BJHBS, we take the opportunity to register our special thanks for the actions of those responsible for sectors of the Universidade do Estado do Rio de Janeiro. In our case, we mention: the Director of Hospital Universitário Pedro Ernesto, the Director of Policlínica Piquet Carneiro, and the Director of the Faculdade de Ciências Médicas. Those actions have permitted the home office of the professionals involved with the preparation of this issue of BJHBS that is now available for you, reader of the BJHBS. Enjoy the reading and take care!